Pertanggungjawaban Tindak Pidana Korporasi Dalam Bidang Perpajakan - Rusito Rusito; Kaboel Suwardi (Faculty of Law, Universitas Wijayakusuma, 2021)
Through this writing the writer conducts a critical analysis of the juridical basis of the criminal scope in Law no. 6 of 1983 as lastly amended by Law No. 16 of 2009 concerning General Provisions and Tax Procedures (UU KUP) which focuses on corporate criminal liability and criminal sanctions related to criminal offenses in the field of taxation. This writing begins with an explanation of criminal liability to corporations as a prerequisite for corporate punishment. The author analyzes criminal offenses in the field of taxation regulated in the KUP Law in terms of legal subjects covered by the KUP Law and criminal sanctions in the event of a violation of these crimes. The author concludes that there are inconsistencies in criminal liability against corporations and the criminal sanctions regulated in Articles 38, 39, and 39A of the KUP Law. The author finally provides some suggestions for improving this law in the aspect of criminal liability for corporations and their criminal sanctions.Keywords: corporate crime, inconsistency, criminal liability.Melalui penulisan ini penulis melakukan telaah secara kritis dasar yuridis dari cakupan pidana dalam Undang-Undang No. 6 Tahun 1983 sebagaimana telah diubah terakhir dengan Undang-Undang No. 16 Tahun 2009 tentang Ketentuan Umum dan Tata Cara Perpajakan (UU KUP) yang berfokus pada pertanggungjawaban pidana korporasi dan sanksi pidana yang terkait dengan pelanggaran tindak pidana di bidang perpajakan. Penulisan ini diawali dengan pemaparan mengenai pertanggungjawaban pidana pada korporasi sebagai suatu prasyarat pemidanaan korporasi. Penulis menganalisis tindak pidana di bidang perpajakan yang diatur dalam UU KUP dalam hal subjek hukum yang dicakup oleh UU KUP dan sanksi pidana dalam hal terjadi pelanggaran tindak pidana tersebut. Penulis menyimpulkan adanya ketidakkonsistenan dalam pertanggungjawaban pidana terhadap korporasi dan sanksi pidananya yang diatur dalam Pasal 38, 39, dan 39A UU KUP. Penulis akhirnya memberikan beberapa saran untuk perbaikan undang-undang ini dalam aspek pertanggungjawaban pidana untuk korporasi dan sanksi pidananya.Kata Kunci: kejahatan korporasi, inkonsistensi, pertanggungjawaban pidana.